PERAN PEMERINTAH DAERAH DALAM PEMBERDAYAAN MASYARAKAT NELAYAN - Windasai Windasai; Mohammad Mas’ud Said; Hayat Hayat (Sekolah Tinggi Pariwisata Mataram, 2021)
This study aims to determine the role of local government in empowering fishing communities, as well as the factors that support and influence it. This study uses a qualitative method with a descriptive approach to the type of case study research. Qualitative descriptive research method is research that is used to describe events or phenomena that occur. Data collection in this study used observation, interviews and documentation techniques. The results of this study are related to the role of local governments in empowering fishing communities, namely organizing fishing community empowerment programs such as increasing human resources, developing facilities and infrastructure and establishing fishermen’s institutions. However, in community, there are still several obstacles, such as the lack of human resources at the Sumenep Regency Fisheries Service, limited budget, lack of adequate technology an transportation. This causes the empowerment of fishing communities to be less than optimal.